ANALISIS KEPUASAN MASYARAKAT TERHADAPPELAYANAN PUBLIK MENGGUNAKAN PENDEKATANPARTIAL LEAST SQUARE (PLS) (Studi Kasus: Badan Arsip dan Perpustakaan Daerah Provinsi Jawa Tengah) - Emyria Natalia br Sembiring; Abdul Hoyyi; Rukun Santoso (Jurnal Gaussian, 2017)
Public service in Indonesia has grown into a strategic policy issue. The implementation of public services in the field of library is intended to provide library services to the public quickly, precisely and accurately. This research aims to analyze the effect between service quality, collection quality, employee performance, user needs (community) on community satisfaction and its implications for community loyalty or interest in library utilization. The use of SEM based covariance with parametric assumption that research variable must fulfill normal multivariate distribution assumption. However, the research variables do not meet the assumptions of normality then used Partial Least Square (PLS). The research was conducted at the Regional Library of Central Java Province. The method of testing instrument used SPSS Software 22.00 and hypothesis testing using Structural Equation Modeling (SEM) by SmartPLS 3.00 software. Characteristics of respondents are women (65,5%), age 21-25 years (53,5%), and job as student (69,5%). The results showed that the variable quality of service, collection quality, and community give a positive and significant effect, while employee performance variable gives positive effect but not significant to the satisfaction of society. The variable of satisfaction has a positive and significant effect on community loyalty. Keywords: Public Service, Library, Partial Least Square (PLS)